Proverb as an Object of Philological Research - Ochilova, Zarifa (Universitas Muhammadiyah Sidoarjo, 2022)
In this article, English and Uzbek folk proverbs are studied in the field of paremiology of folklore and differ from other genres of folklore with a number of peculiarities. In them, the idea is expressed in the form of a clear, complete conclusion, a concise sentence, guided by the expression of a particular sentence in a logical sequence, sharp polarity, and can be used in its own and figurative senses. In addition, the proverbs show their universal nature through the predominance of exemplary, instructive aspects.